(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Working out the details of travel and pleasure takes a lot of time and effort. But as said before, it is a time-consuming process; there are travelers who want to spare the effort of planning their journeys, stays, etc. Rather they would pay someone else to do the entire arrangement. This demand led to the origin of tour operators. A tour operator is a business that typically combines and organizes accommodations, meals, sightseeing and transportation components, in order to create a package tour.